Money and banks: Some theory and empirical evidence for Germany - Oliver Holtemöller (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2002)
In a world with imperfect competition, market externalities or asymmetric information, the impact of money and monetary policy on the real sector depends on the way money is created. Two conflicting views of money supply can be distinguished in the literature: the endogeneity view and the exogeneity view. In this paper, both views are discussed and compared from a theoretical and from an empirical point of view. An industrial organization model of the money-creating sector with endogenous money is presented and compared to the money multiplier approach. The concept of a heterogeneous oligopoly is used to model the credit market and the deposits market. Using the aggregated balance sheet of the banking sector, endogenous money is explained by its counterparts, especially loans. The monetary base is determined endogenously, too, and a money multiplier equivalent expression can be derived. A cointegrated vector autoregressive model for the development of the nominal money stock in Germany in the period of monetary targeting from 1975 to 1998 is estimated. The implications of the theoretical model are compared to the properties of the estimated VAR. It turns out that both the money multiplier approach and the presented model of the money-creating sector with endogenous money fail to explain all the empirical evidence from the VAR model.
urn:nbn:de:kobv:11-10048693
Keywords: C32; E51; E52; 330; monetary policy; Endogenous money; industrial organization approach to banking theory; money multiplier; vector error correction mode